Hypoglycemic medicines in the treatment of Alzheimer’s disease: Pathophysiological links between AD and glucose metabolism - Wang, Yixuan; Hu, Hao; Liu, Xinyu; Guo, Xiangyu (Frontiers in Pharmacology, 2023)
Alzheimer’s Disease (AD) is a global chronic disease in adults with beta-amyloid (Aβ) deposits and hyperphosphorylated tau protein as the pathologic characteristics. Although the exact etiology of AD is still not fully elucidated, aberrant metabolism including insulin signaling and mitochondria dysfunction plays an important role in the development of AD. Binding to insulin receptor substrates, insulin can transport through the blood-brain barrier (BBB), thus mediating insulin signaling pathways to regulate physiological functions. Impaired insulin signaling pathways, including PI3K/Akt/GSK3β and MAPK pathways, could cause damage to the brain in the pathogenesis of AD. Mitochondrial dysfunction and overexpression of TXNIP could also be causative links between AD and DM. Some antidiabetic medicines may have benefits in the treatment of AD. Metformin can be beneficial for cognition improvement in AD patients, although results from clinical trials were inconsistent. Exendin-4 may affect AD in animal models but there is a lack of clinical trials. Liraglutide and dulaglutide could also benefit AD patients in adequate clinical studies but not semaglutide. Dipeptidyl peptidase IV inhibitors (DPP4is) such as saxagliptin, vildagliptin, linagliptin, and sitagliptin could boost cognitive function in animal models. And SGLT2 inhibitors such as empagliflozin and dapagliflozin were also considerably protective against new-onset dementia in T2DM patients. Insulin therapy is a promising therapy but some studies indicated that it may increase the risk of AD. Herbal medicines are helpful for cognitive function and neuroprotection in the brain. For example, polyphenols, alkaloids, glycosides, and flavonoids have protective benefits in cognition function and glucose metabolism. Focusing on glucose metabolism, we summarized the pharmacological mechanism of hypoglycemic drugs and herbal medicines. New treatment approaches including antidiabetic synthesized drugs and herbal medicines would be provided to patients with AD. More clinical trials are needed to produce definite evidence for the effectiveness of hypoglycemic medications.